"ظاهرة المشترﻙ اللفظي في اللغة الترکیة الأذربیجانیة": الکلمات العربیة الدخیلة أنموذجاً / The Phenomenon of homonym in the Turkish-Azerbaijani Language: Arabic vocabulary as a case study - Biyanlu, Ali (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2021)
مُلخَّص البحث: المشترﻙ اللفظي ظاهرة لغویة قد طرأت علی اللغة الترکیة الأذربیجانیة لدی مفرداتها الأصیلة والعربیة الدخیلة. ویتعقّد الأمر عندما تستخدم الأذربیجانیة الأبجدیة اللاتینیة. من هنا، تهدف هذه المقالة، اعتماداً علی المنهج الوصفي والتّحلیلي، إلی البحث عن المشترﻙ اللفظي في الکلمات العربیة الدّخیلة ذات الأصول المتباینة والمکتوبة بالأبجدیة اللاتینیة، وتتابعها من خلال الکلمات المجدولة، وتحلیل العناصر الصوتیة والتصریفیة، بوصفها قناعات لغویة أذربیجانیة. وقد توصلت الدراسة إلى أنّها جعلت القناعات الصوتیة في اللغة الأذربیجانیة والکتابة اللاتینیة لها تفقد الأصوات الخاصة باللغة العربیة؛ منها "ص، ث، ذ، ض، ظ، ط، ح، ع، غ، ء"، فتتشابه إثرها لفظة عربیة مع أخری في الکتابة اللاتینیة، وأنه قد یسهم في حدوث الاشتراﻙ اللفظي وجود العامل الصوتي في اللغة الترکية؛ وهو أن تتناغم الصوائت في الکلمة، وقد تختزل الکلمة بعد حذف "ع" إذا تطرّف، وهذه عارضة تصریفیة خاصّة بالأذربیجانیة في تعاملها مع اللفظ العربي الدخیل، وقد تعمل قناعة اللغة الأذربیجانیة في الاشتراﻙ اللفظي بإقحام "ي" في الکلمات الثلاثیة، فراراً من تسکین الحرف الوسیط، فتتشابه کلمة في کتابتها اللاتینیة مع کلمة أخری، وقد یحدث الاشتراﻙ اللفظي بوصفه عارضة تصریفیة عشوائية في الکتابة الأذربیجانیة بعد التحاق الضمائر بالکلمات، وقد یؤثّر في تألیف الاشتراﻙ اللفظي وجود قناعة لغویة تسمّی القلب اللغوي، والأمر ظاهرة شفهية لهجية أکثر من أن یکون ظاهرة أبجدیة. الکلمات المفتاحیة: اللغة الأذربیجانیة، المشترﻙ اللفظي، الکلمات العربیة الدخیلة. Absract Homonym is a linguistic feature that is found in the Azerbaijani language as a result, among others, of Arabic loan words. It becomes more complicated when Azerbaijani uses the Latin alphabet. This article aims, based on the descriptive-analytical method, to study the homonym in Arabic vocabulary with distinct origins in the Azeri Latin script. Through the tabulated vocabulary, it analyzes the phonemic-morphological elements as Azerbaijani linguistic basics. As a result, the Azeri phonemic basics and its Latin script lost the special Arabic phonemes, such as ṣād, tsa, dza, ḍat, ẓa, ṭa, ḥa, ʿain, ghain, ḥamzah making the Arabic words resembles other ordinary words. The ocuurence of homonym has resulted in a phonetic factor in the Turkish language that witnesses the harmonization of the vowels. The word detracts after deleting “ʿain” from the end of the word. This is a morphological change specifically found in the Azerbaijani language when dealing with the Arabic loan word. The Azeri language deals with homonyms by inserting “ya” into the triple words, to avoid from having the ‘sukūn’ in the middle letter, so that the word in Latin script would resemble other ordinary words. The homonym also occurs as a random morphological form in Azerbaijani script after the attachment of pronouns to words. The formation of homonym might be influenced by the language alternation, but this appears to be more of a verbal colloquial phenomenon rather than an alphabetical one. Keywords: Azeri language, Homonym, Arabic vocabulary. Abstrak Homonim ialah ciri linguistik yang terdapat dalam bahasa Azerbaijan sebagai kesan, antara lain, perkataan pinjaman Arab. Ia menjadi lebih rumit apabila bahasa Azerbaijan menggunakan abjad Latin. Artikel ini bertujuan, berdasarkan kaedah deskriptif-analisis, untuk mengkaji homonim kosa kata Arab dengan asal usul yang berbeza dalam tulisan Latin bahsa Azeri. Melalui perbendaharaan kata yang diletakkan dalam jadual, kajian ini menganalisis unsur fonemik-morfologi sebagai asas linguistik bahasa Azeri. Akibatnya, asas fonemik Azeri dan skrip Latinnya kehilangan fonem Arab yang khusus, seperti ṣād, tsa, dza, ḍat, ẓa, ṭa, ḥa, ʿain, ghain, ḥamzah dan menjadikan perkataan Arab itu menyerupai perkataan biasa yang lain. Kemunculan homonim telah menghasilkan faktor fonetik dalam bahasa Turki yang menyaksikan penyelarasan vokal. Perkataan itu merosot selepas memadamkan "ʿain" dari hujung perkataan. Ini adalah perubahan morfologi yang secara khusus ditemui dalam bahasa Azeri apabila berkenaan dengan perkataan pinjaman Arab. Bahasa Azeri menangani homonim dengan memasukkan "ya" ke dalam tiga huruf asal Arab, untuk mengelakkan daripada mempunyai 'sukūn' di huruf tengah, dan juga supaya perkataan dalam skrip Latin itu akan menyerupai perkataan biasa yang lain. Homonim juga terjadi sebagai satu bentuk morfologi rawak dalam tulisan Azeri selepas ganti nama digabung dengan perkataan. Pembentukan homonim mungkin dipengaruhi oleh perubahan bahasa, tetapi ini nampaknya lebih dipengaruhi oleh sebutan bahasa pasar harian dan bukannya disebabkan oleh faktor abjad. Kata kunci: Bahasa Azeri, Homonim, kosa kata Arab.